Effect of prostaglandins and beta blockers on progression of hypertensive and normotensive glaucomas - Klara Maresova; Jan Lestak; Martin Fus; Iveta Weissova (Biomedical Papers, 2021)
Aim. The aim of the study was to evaluate the progression of changes in the visual fields in patients with hypertensive glaucoma (HTG) and normotensive glaucoma (NTG) following administration of prostaglandins and beta blockers, as well as also in NTG without ophthalmological therapy. Methodos. The HTG group included 12 patients (mean age 66 years) with approximately the same changes in the visual field and central corneal thickness (CCT-568um) treated with prostaglandins, and 12 patients (mean age 60 years, CCT=544um) treated with beta-blockers. The IOP ranged from 12 to 18mmHg for the whole follow-up period. The NTG group consisted of three subgroups. The first subgroup consisted of 14 patients (mean age 58 years) who were treated with prostaglandins. The second subgroup consisted of 10 patients (mean age 57 years) who were treated with beta blockers. The third subgroup consisted of 18 patients (mean age 57 years) who underwent no ophthalmological therapy. IOP was within the range of 8-12 mmHg over the whole follow-up period. In all patients, we monitored the pattern defect (PD) and overall defect (OD) within a period of five years. The treatment was not modified during the treatment period. All patients were compensated for cardiovascular status and had no other internal or neurological disease. Visual acuity was 1.0 with a possible correction (less than 3 dioptres) in all patients. Results. There was no statistically significant difference in HTG during the treatment with prostaglandins in PD (P=0.35) and OD (P=0.09) or beta blockers (P=0.37 and 0.23, respectively). In NTG, the greatest changes occurred in PD (P=0.0001) in untreated patients. OD showed no statistically significant changes (P=0.25). Similarly, the patients on prostaglandins had a statistically significant difference in PD (P=0.04), while OD did not show statistically significant changes (P=0.4). We did not find statistically significant differences in progression in patients with NTG treated with beta blockers PD (P=0.7), OD (P=0.4). Conclusion. Treatment of glaucoma with prostaglandins and beta blockers has a significant importance in HTG. However, beta blockers have a higher protective effect on the visual field. This is not true in NTG, where we demonstrated this effect only following the administration of beta blockers.